2013
DOI: 10.1155/2013/902538
|View full text |Cite
|
Sign up to set email alerts
|

Review on the Synthesis and Applications of Fe3O4 Nanomaterials

Abstract: Recently, Fe3O4nanomaterials have attracted tremendous attention because of their favorable electric and magnetic properties. Fe3O4nanostructures with various morphologies have been successfully synthesized and have been used in many fields such as lithium-ion batteries (LIBs), wastewater treatment, and magnetic resonance imaging (MRI) contrast agents. In this paper, we provide an in-depth discussion of recent development of Fe3O4nanomaterials, including their effective synthetic methods and potential applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 79 publications
(65 reference statements)
0
16
0
1
Order By: Relevance
“…For instance, a study conducted a few years ago found that exposure of BEAS‐2B cells to TiO 2 NPs induced apoptosis and oxidative stress . Another study investigated the effect of TiO 2 NPs on human astrocyte and neuronal cells after acute and long‐term exposure . Both acute and prolonged exposure even at low dose seem to affect the proliferative capacity of the cells.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…For instance, a study conducted a few years ago found that exposure of BEAS‐2B cells to TiO 2 NPs induced apoptosis and oxidative stress . Another study investigated the effect of TiO 2 NPs on human astrocyte and neuronal cells after acute and long‐term exposure . Both acute and prolonged exposure even at low dose seem to affect the proliferative capacity of the cells.…”
Section: Discussionmentioning
confidence: 94%
“…The past decade has seen an explosive growth in the synthesis and use of ENMs . ENMs have applications in various kinds of materials and processes because of their unique electrical, magnetic, optical, and catalytic properties . TiO 2 NPs specifically have varied applications.…”
Section: Discussionmentioning
confidence: 99%
“…Their sizedependent MRI properties together with their superparamagnetic behavior, biocompatibility and chemical stability place them as a particularly important NP type for biomedical applications [83]. IONPs are typically composed of magnetite (Fe3O4) and/or maghemite (γ-Fe2O3) nanocrystals, which may exhibit different shapes (spheres, cubes, rods, rings, flowers, pyramids, etc.).…”
Section: Iron Oxide Nanoparticles (Ionps)mentioning
confidence: 99%
“…[1][2][3][4][5] During the past few years, researchers have proposed various chemical-based synthetic methods for preparing magnetic Fe 3 O 4 nanoparticles, including coprecipitation, sol-gel processing, sonochemical method, microwave synthesis, micro-emulsion and hydrothermal method. 6 Among these synthetic methods, the hydrothermal technique for fabricating crystals of magnetic Fe 3 O 4 nanomaterials is an ideal and promising approach, attracting considerable interest.…”
Section: Introductionmentioning
confidence: 99%